2018
DOI: 10.1538/expanim.18-0045
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of a porcine mitral regurgitation model

Abstract: The porcine mitral regurgitation (MR) model is a common cardiovascular animal model. Standardized manufacturing processes can improve the uniformity and success rate of the model, and systematic research can evaluate its potential use. In this study, 17 pigs were divided into an experimental group (n=11) and a control group (n=6). We used a homemade retractor to cut the mitral chordae via the left atrial appendage to establish a model of MR; the control group underwent a sham surgery. The model animals were fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 43 publications
1
12
0
Order By: Relevance
“…In addition, the valves we used were healthy porcine valves and prolapse was induced by cutting chordae rather than through native pathological processes resulting in chordae elongation and rupture, although this is an accepted model of MR frequently used experimentally. 52 , 53 We did not use an annuloplasty ring in our experiments, which could influence our results given that annuloplasty is the standard of care in addition to repair techniques. We chose not to include annuloplasty ring so as not to confound our results, but they should be interpreted with this limitation in mind.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the valves we used were healthy porcine valves and prolapse was induced by cutting chordae rather than through native pathological processes resulting in chordae elongation and rupture, although this is an accepted model of MR frequently used experimentally. 52 , 53 We did not use an annuloplasty ring in our experiments, which could influence our results given that annuloplasty is the standard of care in addition to repair techniques. We chose not to include annuloplasty ring so as not to confound our results, but they should be interpreted with this limitation in mind.…”
Section: Discussionmentioning
confidence: 99%
“…The valves used in this study were also normal, healthy valves and P2 prolapse was induced by cutting chordae as opposed to natural pathological processes resulting in chordal rupture typical in degenerative valve disease. Nonetheless, this is an accepted model of MR commonly used experimentally [ 28 , 29 ]. Future in vivo investigations currently underway will address some of these limitations.…”
Section: Discussionmentioning
confidence: 99%
“…myocyte hypertrophy, which are the causes of left atrial stiffness [Moustafa 2011;Corradi 2012]. Studies have found a significant negative correlation between LA reservoir strain and myocardial fibrosis [Cameli 2013], a typical pathological change in MR [Li 2018;Cameli 2013]. These studies share our view that a large variety of ultrastructural changes and degeneration, including interstitial fibrosis and cellular degenerative changes, were present in patients undergoing cardiac surgery for mitral valvular disease.…”
Section: E750mentioning
confidence: 88%
“…The LV can pump excess blood into the low-pressure LA and result in increased LA pressure and volume load. This makes the LA the most severely affected cardiac chamber, with functional impairment at the early stage of MR. Changes in left atrial volume (LAV) and function may be earlier and substantial than those in the LV [Li 2018], so an in-depth study of LA function and size may provide deeper insight into the pathophysiology of MR and a reference for disease stage.…”
Section: Introductionmentioning
confidence: 99%